Health Consequences of Childhood and Adolescence Shocks: Is There a "Critical Period"? - Valeria Groppo (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Individual health is not only determined by genetic factors, but also by negative or positive events during the life course. For example, children exposed to natural disasters or violent conflicts are more likely to have poor health as adults. Positiveexternal factors, such as nutritional programs, will, instead, improve individual health in the long-term. In turn, health can directly affect education and income opportunities, with macroeconomic consequences for economic growth. In particular,this Roundup investigates the following question: is there an age when shocks or interventions can have a magnified effect? In other words, is there a time while growing up when individual health is more responsive to external events? This is a relevant question, since timing represents a crucial dimension of health interventions. Available evidence identifies several sensitive periods, providing useful lessons for health policy with important economic implications.
Keywords: 330